Clinical Pattern and Associated Comorbidities of Corpus Callosum Agenesis- A Tertiary Hospital Study - Kundu, Gopen Kumar; Anower, Anjir; Islam, Rumana (Bangladesh Journal of Child Health, 2021)
Background: The corpus callosum is the main commissural bundle of fibers interconnecting the two cerebral hemispheres. Defective embryogenesis during 8 and 20 weeks of gestation can lead to partial or complete agenesis of the corpus callosum. Objective: To see the patient’s clinical, neurophysiological profile, and comorbidities with corpus callosum agenesis presented in tertiary care hospital. Materials &Methods: This descriptive cross-sectional study was conducted in the department of Paediatric Neurology, BSMMU, Dhaka, from January to December 2018. Patients who were diagnosed clinically and neuro-radiologically as corpus callosum agenesis were included in this study. Results:Out of 20 patients, 45% were in 13-24 months and 30% were in the 0-12 months’ age group. Female patients (55%) were predominant.Forty percent of patients had microcephaly and 30% facial dysmorphism. The majority of patients presented with developmental delay (90%), followed by epilepsy, speech impairment, and mental retardation. About one-fourth (25%) of patients were diagnosed as quadriplegic cerebral palsy and one-third (30%) dyskinetic cerebral palsy. Abnormal ophthalmological findings were found in 40% of cases. EEG showed hypsarrhythmia in 30%, partial seizure with secondary generalization in 15%, and myoclonic epilepsy in 15% of patients. Conclusion: In this study, common clinical features of patients with corpus callosal agenesis were developmental delay, facial dysmorphism, and microcephaly. About half of the patients had epilepsy, speech impairment, and mental retardation. About two-thirds of the patients had EEG changes and the most common EEG change was hypsarrhythmia. BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 10-14